Inovasi Layanan Pengaduan Online “Lapor Padang” Dalam Meningkatkan Akuntabilitas Pemerintah Kota Padang - Nabila Laila Rani; Miftahul Hasanah; Rifha Tri Oktary; Zara Handayani; Yulia Hanoselina; Yuliarti . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Public service issues are still characterized by a suboptimal public complaints system, service transparency, and government response to public reports. This study aims to analyze the innovation of the complaint service "Lapor Padang" in improving the accountability of the Padang City Government. This study uses the theory of public service innovation as a basis for analyzing the implementation of the complaint service "Lapor Padang" in improving public service accountability in Padang City. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation at the Padang City Communication and Informatics Office. The results show that the "Lapor Padang" service makes it easier for the public to submit complaints, increases the responsiveness of Regional Apparatus Organizations (OPD), and strengthens transparency through a report tracking system. However, its implementation still faces obstacles in the form of suboptimal inter-agency coordination, limited human resources, and low digital literacy among the community. Overall, the "Lapor Padang" service contributes to improving the accountability and quality of public services in Padang City.